Meeting Ghanaian farmers' demand for a full range of mechanization services - Houssou, Nazaire; Aboagye, Patrick Ohene; Kolavalli, Shashidhara (International Food Policy Research Institute, 2016)
Rising labor costs associated with increased rural-to-urban migration have compelled Ghanaian farmers to increase the use of tractors and other agricultural machines to conduct farming operations in the country (Diao et al. 2014). The adoption of these mechanical technologies is consistent with the tendency among Ghanaian farmers to save labor, rather than embrace practices that create additional labor needs (Houssou et al. 2016). Tractor use is concentrated on plowing and other tillage operations primarily (Houssou et al. 2013), but the supply of tractor services is inadequate. Earlier research estimated that plowing services represent 90 percent of the revenues of tractor service providers (Houssou et al. 2013). Both public and private supply of plowing services may have contributed to an expan-sion of the area under cultivation in Ghana, thereby exacerbat-ing labor bottlenecks in post-tillage field operations for many farmers.